1981
DOI: 10.1007/bf00302840
|View full text |Cite
|
Sign up to set email alerts
|

Social organization and kinship in the polygynous bat Phyllostomus hastatus

Abstract: 1. Social behavior in the bat Phyllostomus hastatus was examined in Trinidad, W.I. over a 26month period. The studies included (a) long-term observations on marked individuals, (b) the use of allozyme polymorphisms to estimate paternity and the genetic relationships among individuals in social groups, and (c) the investigation of foraging behavior by radio-tracking. 2. Day-roosting cave colonies of this bat are subdivided into highly stable, compact clusters of adult females (mean cluster size = 17.9 + 5.1 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
157
0
7

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(174 citation statements)
references
References 52 publications
10
157
0
7
Order By: Relevance
“…Although two birth peaks (April and October) have been reported for greater spear-nosed bat populations in Colombia and Venezuela, births outside late March to early May are rare on Trinidad and in Nicaragua and Panama (James, 1977;Wilson, 1979;McCracken & Bradbury, 1981). In addition to a relatively short birth season in Trinidad, McCracken & Bradbury (1981) found temporal clustering of births within caves. Furthermore, within each cave, the similarity among pup ages seemed to be greater within than across social groups.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although two birth peaks (April and October) have been reported for greater spear-nosed bat populations in Colombia and Venezuela, births outside late March to early May are rare on Trinidad and in Nicaragua and Panama (James, 1977;Wilson, 1979;McCracken & Bradbury, 1981). In addition to a relatively short birth season in Trinidad, McCracken & Bradbury (1981) found temporal clustering of births within caves. Furthermore, within each cave, the similarity among pup ages seemed to be greater within than across social groups.…”
Section: Introductionmentioning
confidence: 96%
“…Females form stable social groups of eight to 40 individuals who are not closely related (McCracken & Bradbury, 1981;McCracken, 1987). The females spend most of the day pressed against groupmates in the same solution depression in a cave ceiling, year after year, thereby affording considerable opportunity for the exchange of chemical or other social cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since roosts may have different sex ratios (MCCRAKEN;BRADBURY, 1981;COSTA et al, 2010), different prevalence and intensity values may be observed, as in the present study. Constant roost changes may also be responsible for re-infestation and dispersal of ectoparasites within the bat population.…”
Section: Discussionmentioning
confidence: 57%
“…Females of P. hastatus have broader interspecific interactions and higher roost fidelity (MCCRAKEN;BRADBURY, 1981). Harems are stable, with females living together for consecutive years, whereas long cohesion has not been observed in bachelor groups.…”
Section: Discussionmentioning
confidence: 99%